High-strength light extra-high voltage electric porcelain blank and preparation method thereof

By using modified silica powder and other components in electroceramic blanks, combined with technical means of doping cerium, tannin modification and grafting β-cyclodextrin, the high strength and plasticity requirements in electroceramic insulator molding are solved. The problem of high-strength and low-cost electroceramic blank preparation has been achieved.

CN119430855AActive Publication Date: 2025-02-14PINGXIANG HIGH CLASS INSULATOR CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411659860.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-14
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The prior art is difficult to meet the high requirements for blank strength and plasticity during the process of electroceramic insulator molding, and clay raw materials alone cannot meet the manufacturing needs of complex product structures.

Method used

A high-strength lightweight ultra-high voltage electro-electrochemical blank is used, with raw materials including clay, porcelain powder, modified silica powder, potassium feldspar, bauxite powder, humic acid and titanium dioxide powder, and doped with cerium elements and tannin acid Modification and grafting β-cyclodextrin and other steps to improve the binding force and cross-linking effect between silica and other component particles.

Benefits of technology

It significantly improves the strength of the ceramic blank, ensures the smooth progress of subsequent processes, reduces the damage rate, and reduces production and processing costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-strength light extra-high-voltage electric porcelain blank which is prepared from the following raw materials: clay, porcelain powder, modified silicon dioxide powder, potassium feldspar, bauxite powder, humic acid and titanium dioxide powder. The raw materials comprise, by weight, 100 parts of clay, 20-30 parts of porcelain powder, 20-25 parts of modified silicon dioxide powder, 24-28 parts of potassium feldspar, 16-20 parts of bauxite powder, 0.6-0.8 part of humic acid, and 6-10 parts of titanium dioxide powder. The electroceramic blank prepared by the method has good strength, can effectively ensure smooth proceeding of subsequent fettling, glazing, kiln loading and other procedures, reduces the breakage rate, and reduces the production and processing cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electric porcelain blank materials, and in particular to a high-strength and lightweight ultra-high voltage electric porcelain blank and a preparation method thereof. Background Art

[0002] Different from other ceramic products, electric porcelain insulators have different product structures and process flows, and therefore require very high strength and plasticity of the blanks. With the rapid development of the electric porcelain industry in my country, the high-quality plastic clay raw materials that the industry has been using are becoming increasingly scarce. However, the development of power transmission and transformation has placed higher and higher performance requirements on electric porcelain insulators, and the product structure has become more complex. The molding process also requires higher and higher strength and plasticity of the blank mud. Clay raw materials alone can no longer meet the requirements of the product manufacturing process for blank strength and plasticity. Summary of the invention

[0003] To this end, the present invention provides a high-strength, lightweight, ultra-high voltage electric porcelain blank, the raw materials of which include clay, porcelain powder, modified silicon dioxide powder, potassium feldspar, bauxite powder, humic acid and titanium dioxide powder; wherein the preparation method of the modified silicon dioxide powder is:

[0004] (1) preparing an ethanol solution of tetraethyl orthosilicate; preparing a mixed solution of ammonia water and ethanol; preparing an aqueous solution of cerium nitrate; heating the ethanol solution of tetraethyl orthosilicate in a water bath to 60±5° C. and keeping it warm, condensing and refluxing during the keeping warm process; then adding the mixed solution of ammonia water and ethanol and the aqueous solution of cerium nitrate to the ethanol solution of tetraethyl orthosilicate at the same time under stirring, continuing to stir at a constant temperature of 60±5° C. for 80 to 100 minutes after the addition is completed, then standing at room temperature for more than 5 hours, separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, and then drying at 200° C. for more than 3 hours to obtain doped silicon dioxide powder;

[0005] (2) adding the doped silica powder to an aqueous solution of ethanol, stirring and dispersing for more than 20 minutes under an ultrasonic environment to obtain a dispersion; then adding tannic acid to the dispersion under stirring, adjusting the pH of the dispersion to 4-6 after the addition is completed, and then heating the dispersion to 80±5° C. in a water bath, stirring at a constant temperature for more than 60 minutes, separating the solid and the liquid after the stirring is completed, washing the solid phase with deionized water for more than 3 times, and drying at 80° C. for more than 3 hours to obtain a modified powder;

[0006] (3) preparing an N,N-dimethylformamide solution of β-cyclodextrin, stirring the N,N-dimethylformamide solution of β-cyclodextrin, and then adding 1,1'-carbonyldiimidazole to the solution under stirring, and continuing to stir the solution for more than 2 hours after the addition is completed, and then adding the modified powder to the solution under stirring, and continuing to stir for more than 15 hours after the addition is completed, and then separating the solid and the liquid, washing the solid phase with N,N-dimethylformamide for more than 2 times, and then washing with deionized water for more than 2 times to obtain the modified silica powder.

[0007] Furthermore, the raw materials are calculated by weight as follows: 100 parts of clay, 20-30 parts of porcelain powder, 20-25 parts of modified silicon dioxide powder, 24-28 parts of potassium feldspar, 16-20 parts of bauxite powder, 0.6-0.8 parts of humic acid, and 6-10 parts of titanium dioxide powder.

[0008] Furthermore, in the step (1), in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 5% to 6%, and the solvent is ethanol; the mixed solution of ammonia water and ethanol is prepared by mixing ammonia water with a solute mass percentage of 25% and anhydrous ethanol in a volume ratio of ammonia water: anhydrous ethanol = 2 to 3:1; and in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 8 to 10 g / L.

[0009] Furthermore, in the step (1), the volume ratio of the mixed solution of ammonia water and ethanol and the aqueous solution of cerium nitrate added to the ethanol solution of tetraethyl orthosilicate is ethanol solution of tetraethyl orthosilicate: the mixed solution of ammonia water and ethanol: the aqueous solution of cerium nitrate = 10:4-5:1-2.

[0010] Furthermore, in the step (2), the mass ratio of the doped silica powder added to the ethanol aqueous solution is doped silica powder: ethanol aqueous solution = 1:30-40; wherein the volume percentage of ethanol in the ethanol aqueous solution is 80%-85%, and the rest is water; the mass ratio of the added mass of tannic acid to the mass ratio of the doped silica powder added when preparing the dispersion is doped silica powder: tannic acid = 1:0.5-0.8.

[0011] Furthermore, in the step (3), the concentration of β-cyclodextrin in the N,N-dimethylformamide solution of β-cyclodextrin is 16-20 g / L, and the solvent is N,N-dimethylformamide; the volume ratio of the added mass of the 1,1'-carbonyldiimidazole and the modified powder to the N,N-dimethylformamide solution of β-cyclodextrin is 1,1'-carbonyldiimidazole: modified powder: N,N-dimethylformamide solution of β-cyclodextrin = 3-4 g: 1-3 g: 100 mL.

[0012] The beneficial effects of the present invention are as follows: the electric porcelain blank prepared by the method of the present invention has good strength, can effectively ensure the smooth progress of subsequent blank repairing, glazing, kiln loading and other processes, reduce the breakage rate, and reduce the production and processing costs. The present invention firstly dopes cerium into silicon oxide, and the obtained doped silica powder has a higher specific surface area, which on the one hand significantly increases the bonding surface between silica powder and other components in the subsequent blank, and on the other hand also prepares for the subsequent surface modification. Then, through tannic acid modification, a macromolecular structure is formed on the powder surface, so that the bonding force between silica and clay particles is enhanced, thereby improving the strength of the blank. Subsequent grafting of β-cyclodextrin can further improve the cross-linking effect between silica and other component particles, forming an irregular network structure with modified silica powder as a connecting unit, which has a good improvement effect on the strength of the blank. DETAILED DESCRIPTION

[0013] The present invention will be further described below in conjunction with the embodiments.

[0014] Example 1

[0015] A high-strength, lightweight, ultra-high voltage electric porcelain blank, the raw materials include clay, porcelain powder, modified silicon dioxide powder, potassium feldspar, bauxite powder, humic acid and titanium dioxide powder; each of the raw materials is calculated by weight as follows: 100 parts of clay, 20 parts of porcelain powder, 20 parts of modified silicon dioxide powder, 24 parts of potassium feldspar, 16 parts of bauxite powder, 0.6 parts of humic acid, and 6 parts of titanium dioxide powder. The preparation method of the modified silicon dioxide powder is:

[0016] (1) preparing an ethanol solution of tetraethyl orthosilicate; preparing a mixed solution of ammonia water and ethanol; preparing an aqueous solution of cerium nitrate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 5%, and the solvent is ethanol; the mixed solution of ammonia water and ethanol is prepared by mixing ammonia water with a solute mass percentage of 25% and anhydrous ethanol in a volume ratio of ammonia water: anhydrous ethanol = 2:1; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 8g / L, and the solvent is water; heating the ethanol solution of tetraethyl orthosilicate to 60°C in a water bath and keeping it warm, condensing back during the keeping warm process; flow; then, under stirring, the mixed solution of ammonia water and ethanol and the aqueous solution of cerium nitrate are added to the ethanol solution of tetraethyl orthosilicate at the same time, and the volume ratio of the mixed solution of ammonia water and ethanol and the aqueous solution of cerium nitrate added to the ethanol solution of tetraethyl orthosilicate is ethanol solution of tetraethyl orthosilicate: mixed solution of ammonia water and ethanol: aqueous solution of cerium nitrate = 10:4:1; after the addition is completed, the mixture is stirred at a constant temperature of 60°C for 80 minutes, and then allowed to stand at room temperature for 5 hours, solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and then dried at 200°C for 3 hours to obtain doped silicon dioxide powder;

[0017] (2) adding the doped silica powder to an aqueous solution of ethanol, wherein the mass ratio of the doped silica powder to the aqueous solution of ethanol is doped silica powder: ethanol aqueous solution = 1:30; wherein the volume percentage of ethanol in the aqueous solution of ethanol is 80%, and the rest is water; stirring and dispersing for 20 minutes under an ultrasonic environment to obtain a dispersion; then adding tannic acid to the dispersion under stirring, wherein the mass ratio of the added tannic acid to the mass of the doped silica powder added when preparing the dispersion is doped silica powder: tannic acid = 1:0.5; after the addition is completed, adjusting the pH of the dispersion to 5 (adjusting with acetic acid or ammonia water with a solute mass fraction of 20%), then heating in a water bath to 80°C, stirring at a constant temperature for 60 minutes, and after the stirring is completed, separating the solid and liquid, washing the solid phase with deionized water 3 times, and drying at 80°C for 3 hours to obtain a modified powder;

[0018] (3) preparing a β-cyclodextrin N,N-dimethylformamide solution, wherein the concentration of β-cyclodextrin in the β-cyclodextrin N,N-dimethylformamide solution is 16 g / L and the solvent is N,N-dimethylformamide; stirring the β-cyclodextrin N,N-dimethylformamide solution, and then adding 1,1'-carbonyldiimidazole to the solution under stirring, and continuing to stir the solution for 2 hours after the addition is completed, and then adding the modified powder to the solution under stirring, The volume ratio of the added mass of the 1,1'-carbonyldiimidazole and the modified powder to the N,N-dimethylformamide solution of β-cyclodextrin is 1,1'-carbonyldiimidazole: modified powder: N,N-dimethylformamide solution of β-cyclodextrin = 3g: 1g: 100mL; after the addition is completed, stirring is continued for 15 hours, and then the solid-liquid is separated, and the solid phase is first washed twice with N,N-dimethylformamide and then washed twice with deionized water to obtain the modified silicon dioxide powder.

[0019] The preparation method of the above-mentioned electric porcelain blank is:

[0020] Step 1, weigh the raw materials according to the above weight proportions, mix the raw materials in a ball mill, add water and ball mill, the ball mill speed is 100r / min, the material ball water mass ratio is material: ball: water = 1:1.5:1, and the ball milling time is 10h;

[0021] Step 2: The mixed mud is subjected to vacuum mud refining in a mud refiner, and the air pressure is set to 0.06 MPa;

[0022] Step 3: After refining the mud, the moisture content of the mud is adjusted to 21wt%, and then injected into a mold to form an insulator shape; then dried to a moisture content of 0.1wt%, demolded, and the insulator blank is formed.

[0023] Example 2

[0024] A high-strength, lightweight, ultra-high voltage electric porcelain blank, the raw materials include clay, porcelain powder, modified silicon dioxide powder, potassium feldspar, bauxite powder, humic acid and titanium dioxide powder; the raw materials are calculated by weight as follows: 100 parts of clay, 24 parts of porcelain powder, 22 parts of modified silicon dioxide powder, 26 parts of potassium feldspar, 18 parts of bauxite powder, 0.7 parts of humic acid, and 8 parts of titanium dioxide powder. The preparation method of the modified silicon dioxide powder is:

[0025] (1) preparing an ethanol solution of tetraethyl orthosilicate; preparing a mixed solution of ammonia water and ethanol; preparing an aqueous solution of cerium nitrate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 5%, and the solvent is ethanol; the mixed solution of ammonia water and ethanol is prepared by mixing ammonia water with a solute mass percentage of 25% and anhydrous ethanol in a volume ratio of ammonia water: anhydrous ethanol = 2:1; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 9 g / L, and the solvent is water; heating the ethanol solution of tetraethyl orthosilicate to 60° C. in a water bath and keeping it warm, condensing back during the keeping warm process; flow; then, under stirring, the mixed solution of ammonia water and ethanol and the aqueous solution of cerium nitrate are added to the ethanol solution of tetraethyl orthosilicate at the same time, and the volume ratio of the mixed solution of ammonia water and ethanol and the aqueous solution of cerium nitrate added to the ethanol solution of tetraethyl orthosilicate is ethanol solution of tetraethyl orthosilicate: mixed solution of ammonia water and ethanol: aqueous solution of cerium nitrate = 10:4:1; after the addition is completed, the mixture is stirred at a constant temperature of 60°C for 80 minutes, and then allowed to stand at room temperature for 5 hours, solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and then dried at 200°C for 3 hours to obtain doped silicon dioxide powder;

[0026] (2) adding the doped silica powder to an aqueous solution of ethanol, wherein the mass ratio of the doped silica powder to the aqueous solution of ethanol is doped silica powder: ethanol aqueous solution = 1:30; wherein the volume percentage of ethanol in the aqueous solution of ethanol is 80%, and the rest is water; stirring and dispersing for 20 minutes under an ultrasonic environment to obtain a dispersion; then adding tannic acid to the dispersion under stirring, wherein the mass ratio of the added tannic acid to the mass of the doped silica powder added when preparing the dispersion is doped silica powder: tannic acid = 1:0.6; after the addition is completed, adjusting the pH of the dispersion to 5 (adjusting with acetic acid or ammonia water with a solute mass fraction of 20%), then heating in a water bath to 80°C, stirring at a constant temperature for 60 minutes, and after the stirring is completed, separating the solid and liquid, washing the solid phase with deionized water 3 times, and drying at 80°C for 3 hours to obtain a modified powder;

[0027] (3) preparing a β-cyclodextrin N,N-dimethylformamide solution, wherein the concentration of β-cyclodextrin in the β-cyclodextrin N,N-dimethylformamide solution is 18 g / L and the solvent is N,N-dimethylformamide; stirring the β-cyclodextrin N,N-dimethylformamide solution, and then adding 1,1'-carbonyldiimidazole to the solution under stirring, and continuing to stir the solution for 2 hours after the addition is completed, and then adding the modified powder to the solution under stirring, The volume ratio of the added mass of the 1,1'-carbonyldiimidazole and the modified powder to the N,N-dimethylformamide solution of β-cyclodextrin is 1,1'-carbonyldiimidazole: modified powder: N,N-dimethylformamide solution of β-cyclodextrin = 3g: 2g: 100mL; after the addition is completed, stirring is continued for 15 hours, and then the solid-liquid is separated, and the solid phase is first washed twice with N,N-dimethylformamide and then washed twice with deionized water to obtain the modified silicon dioxide powder.

[0028] The preparation method of the above-mentioned electric porcelain blank is:

[0029] Step 1, weigh the raw materials according to the above weight proportions, mix the raw materials in a ball mill, add water and ball mill, the ball mill speed is 100r / min, the material ball water mass ratio is material: ball: water = 1:1.5:1, and the ball milling time is 10h;

[0030] Step 2: The mixed mud is subjected to vacuum mud refining in a mud refiner, and the air pressure is set to 0.06 MPa;

[0031] Step 3: After refining the mud, the moisture content of the mud is adjusted to 21wt%, and then injected into a mold to form an insulator shape; then dried to a moisture content of 0.1wt%, demolded, and the insulator blank is formed.

[0032] Example 3

[0033] A high-strength, lightweight, ultra-high voltage electric porcelain blank, the raw materials include clay, porcelain powder, modified silicon dioxide powder, potassium feldspar, bauxite powder, humic acid and titanium dioxide powder; the raw materials are calculated by weight as follows: 100 parts of clay, 28 parts of porcelain powder, 24 parts of modified silicon dioxide powder, 26 parts of potassium feldspar, 18 parts of bauxite powder, 0.7 parts of humic acid, and 8 parts of titanium dioxide powder. The preparation method of the modified silicon dioxide powder is:

[0034] (1) preparing an ethanol solution of tetraethyl orthosilicate; preparing a mixed solution of ammonia water and ethanol; preparing an aqueous solution of cerium nitrate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 6%, and the solvent is ethanol; the mixed solution of ammonia water and ethanol is prepared by mixing ammonia water with a solute mass percentage of 25% and anhydrous ethanol in a volume ratio of ammonia water: anhydrous ethanol = 3:1; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 9 g / L, and the solvent is water; heating the ethanol solution of tetraethyl orthosilicate to 60° C. in a water bath and keeping it warm, condensing back during the keeping warm process; flow; then, under stirring, the mixed solution of ammonia water and ethanol and the aqueous solution of cerium nitrate are added to the ethanol solution of tetraethyl orthosilicate at the same time, and the volume ratio of the mixed solution of ammonia water and ethanol and the aqueous solution of cerium nitrate added to the ethanol solution of tetraethyl orthosilicate is ethanol solution of tetraethyl orthosilicate: mixed solution of ammonia water and ethanol: aqueous solution of cerium nitrate = 10:5:2; after the addition is completed, the mixture is stirred at a constant temperature of 60°C for 80 minutes, and then allowed to stand at room temperature for 5 hours, solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and then dried at 200°C for 3 hours to obtain doped silicon dioxide powder;

[0035] (2) adding the doped silica powder to an aqueous solution of ethanol, wherein the mass ratio of the doped silica powder to the aqueous solution of ethanol is doped silica powder: ethanol aqueous solution = 1:30; wherein the volume percentage of ethanol in the aqueous solution of ethanol is 80%, and the rest is water; stirring and dispersing for 20 minutes under an ultrasonic environment to obtain a dispersion; then adding tannic acid to the dispersion under stirring, wherein the mass ratio of the added tannic acid to the mass of the doped silica powder added when preparing the dispersion is doped silica powder: tannic acid = 1:0.7; after the addition is completed, adjusting the pH of the dispersion to 5 (adjusting with acetic acid or ammonia water with a solute mass fraction of 20%), then heating in a water bath to 80°C, stirring at a constant temperature for 60 minutes, and after the stirring is completed, separating the solid and liquid, washing the solid phase with deionized water 3 times, and drying at 80°C for 3 hours to obtain a modified powder;

[0036] (3) preparing a β-cyclodextrin N,N-dimethylformamide solution, wherein the concentration of β-cyclodextrin in the β-cyclodextrin N,N-dimethylformamide solution is 18 g / L and the solvent is N,N-dimethylformamide; stirring the β-cyclodextrin N,N-dimethylformamide solution, and then adding 1,1'-carbonyldiimidazole to the solution under stirring, and continuing to stir the solution for 2 hours after the addition is completed, and then adding the modified powder to the solution under stirring, The volume ratio of the added mass of the 1,1'-carbonyldiimidazole and the modified powder to the N,N-dimethylformamide solution of β-cyclodextrin is 1,1'-carbonyldiimidazole: modified powder: N,N-dimethylformamide solution of β-cyclodextrin = 4g: 2g: 100mL; after the addition is completed, stirring is continued for 15 hours, and then the solid-liquid is separated, and the solid phase is first washed twice with N,N-dimethylformamide and then washed twice with deionized water to obtain the modified silicon dioxide powder.

[0037] The preparation method of the above-mentioned electric porcelain blank is:

[0038] Step 1, weigh the raw materials according to the above weight proportions, mix the raw materials in a ball mill, add water and ball mill, the ball mill speed is 100r / min, the material ball water mass ratio is material: ball: water = 1:1.5:1, and the ball milling time is 10h;

[0039] Step 2: The mixed mud is subjected to vacuum mud refining in a mud refiner, and the air pressure is set to 0.06 MPa;

[0040] Step 3: After refining the mud, the moisture content of the mud is adjusted to 21wt%, and then injected into a mold to form an insulator shape; then dried to a moisture content of 0.1wt%, demolded, and the insulator blank is formed.

[0041] Example 4

[0042] A high-strength, lightweight, ultra-high voltage electric porcelain blank, the raw materials include clay, porcelain powder, modified silicon dioxide powder, potassium feldspar, bauxite powder, humic acid and titanium dioxide powder; the raw materials are calculated by weight as follows: 100 parts of clay, 30 parts of porcelain powder, 25 parts of modified silicon dioxide powder, 28 parts of potassium feldspar, 20 parts of bauxite powder, 0.8 parts of humic acid, and 10 parts of titanium dioxide powder. The preparation method of the modified silicon dioxide powder is:

[0043] (1) preparing an ethanol solution of tetraethyl orthosilicate; preparing a mixed solution of ammonia water and ethanol; preparing an aqueous solution of cerium nitrate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 6%, and the solvent is ethanol; the mixed solution of ammonia water and ethanol is prepared by mixing ammonia water with a solute mass percentage of 25% and anhydrous ethanol in a volume ratio of ammonia water: anhydrous ethanol = 3:1; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 10g / L, and the solvent is water; the ethanol solution of tetraethyl orthosilicate is heated in a water bath to 60°C and kept warm, and condensed back during the heat preservation process flow; then, under stirring, the mixed solution of ammonia water and ethanol and the aqueous solution of cerium nitrate are added to the ethanol solution of tetraethyl orthosilicate at the same time, and the volume ratio of the mixed solution of ammonia water and ethanol and the aqueous solution of cerium nitrate added to the ethanol solution of tetraethyl orthosilicate is ethanol solution of tetraethyl orthosilicate: mixed solution of ammonia water and ethanol: aqueous solution of cerium nitrate = 10:5:2; after the addition is completed, the mixture is stirred at a constant temperature of 60°C for 80 minutes, and then allowed to stand at room temperature for 5 hours, solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and then dried at 200°C for 3 hours to obtain doped silicon dioxide powder;

[0044] (2) adding the doped silica powder to an aqueous solution of ethanol, wherein the mass ratio of the doped silica powder to the aqueous solution of ethanol is doped silica powder: ethanol aqueous solution = 1:30; wherein the volume percentage of ethanol in the aqueous solution of ethanol is 80%, and the rest is water; stirring and dispersing for 20 minutes under an ultrasonic environment to obtain a dispersion; then adding tannic acid to the dispersion under stirring, wherein the mass ratio of the added tannic acid to the mass of the doped silica powder added when preparing the dispersion is doped silica powder: tannic acid = 1:0.8; after the addition is completed, adjusting the pH of the dispersion to 5 (adjusting with acetic acid or ammonia water with a solute mass fraction of 20%), then heating in a water bath to 80°C, stirring at a constant temperature for 60 minutes, and after the stirring is completed, separating the solid and liquid, washing the solid phase with deionized water for 3 times, and drying at 80°C for 3 hours to obtain a modified powder;

[0045] (3) preparing a β-cyclodextrin N,N-dimethylformamide solution, wherein the concentration of β-cyclodextrin in the β-cyclodextrin N,N-dimethylformamide solution is 20 g / L and the solvent is N,N-dimethylformamide; stirring the β-cyclodextrin N,N-dimethylformamide solution, and then adding 1,1'-carbonyldiimidazole to the solution under stirring, and continuing to stir the solution for 2 hours after the addition is completed, and then adding the modified powder to the solution under stirring, The volume ratio of the added mass of the 1,1'-carbonyldiimidazole and the modified powder to the N,N-dimethylformamide solution of β-cyclodextrin is 1,1'-carbonyldiimidazole: modified powder: N,N-dimethylformamide solution of β-cyclodextrin = 4g: 3g: 100mL; after the addition is completed, stirring is continued for 15 hours, and then the solid-liquid is separated, and the solid phase is first washed twice with N,N-dimethylformamide and then washed twice with deionized water to obtain the modified silicon dioxide powder.

[0046] The preparation method of the above-mentioned electric porcelain blank is:

[0047] Step 1, weigh the raw materials according to the above weight proportions, mix the raw materials in a ball mill, add water and ball mill, the ball mill speed is 100r / min, the material ball water mass ratio is material: ball: water = 1:1.5:1, and the ball milling time is 10h;

[0048] Step 2: The mixed mud is subjected to vacuum mud refining in a mud refiner, and the air pressure is set to 0.06 MPa;

[0049] Step 3: After refining the mud, the moisture content of the mud is adjusted to 21wt%, and then injected into a mold to form an insulator shape; then dried to a moisture content of 0.1wt%, demolded, and the insulator blank is formed.

[0050] Comparative Example 1

[0051] A comparative electric porcelain blank, the raw materials include clay, porcelain powder, modified silicon dioxide powder, potassium feldspar, bauxite powder, humic acid and titanium dioxide powder; each of the raw materials is calculated by weight: 100 parts of clay, 28 parts of porcelain powder, 24 parts of modified silicon dioxide powder, 26 parts of potassium feldspar, 18 parts of bauxite powder, 0.7 parts of humic acid, and 8 parts of titanium dioxide powder. The preparation method of the modified silicon dioxide powder is:

[0052] (1) preparing an ethanol solution of tetraethyl orthosilicate; preparing a mixed solution of ammonia water and ethanol; preparing an aqueous solution of cerium nitrate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 6%, and the solvent is ethanol; the mixed solution of ammonia water and ethanol is prepared by mixing ammonia water with a solute mass percentage of 25% and anhydrous ethanol in a volume ratio of ammonia water: anhydrous ethanol = 3:1; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 9 g / L, and the solvent is water; heating the ethanol solution of tetraethyl orthosilicate to 60° C. in a water bath and keeping it warm, condensing back during the keeping warm process; flow; then, under stirring, the mixed solution of ammonia water and ethanol and the aqueous solution of cerium nitrate are added to the ethanol solution of tetraethyl orthosilicate at the same time, and the volume ratio of the mixed solution of ammonia water and ethanol and the aqueous solution of cerium nitrate added to the ethanol solution of tetraethyl orthosilicate is ethanol solution of tetraethyl orthosilicate: mixed solution of ammonia water and ethanol: aqueous solution of cerium nitrate = 10:5:2; after the addition is completed, the mixture is stirred at a constant temperature of 60°C for 80 minutes, and then allowed to stand at room temperature for 5 hours, solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and then dried at 200°C for 3 hours to obtain doped silicon dioxide powder;

[0053] (2) preparing a β-cyclodextrin N,N-dimethylformamide solution, wherein the concentration of β-cyclodextrin in the β-cyclodextrin N,N-dimethylformamide solution is 18 g / L and the solvent is N,N-dimethylformamide; stirring the β-cyclodextrin N,N-dimethylformamide solution, and then adding 1,1'-carbonyldiimidazole to the solution under stirring, and continuing to stir the solution for 2 hours after the addition is completed, and then adding the doped silica powder to the solution under stirring, and the 1,1'-carbonyldiimidazole is added to the solution under stirring. The volume ratio of the added mass of 1'-carbonyldiimidazole and the doped silica powder to the N,N-dimethylformamide solution of β-cyclodextrin is 1,1'-carbonyldiimidazole: doped silica powder: β-cyclodextrin N,N-dimethylformamide solution = 4g: 2g: 100mL; after the addition is completed, stirring is continued for 15h, and then the solid-liquid is separated, and the solid phase is first washed twice with N,N-dimethylformamide and then washed twice with deionized water to obtain the modified silica powder described in this comparative example.

[0054] The preparation method of the above-mentioned electric porcelain blank is:

[0055] Step 1, weigh the raw materials according to the above weight proportions, mix the raw materials in a ball mill, add water and ball mill, the ball mill speed is 100r / min, the material ball water mass ratio is material: ball: water = 1:1.5:1, and the ball milling time is 10h;

[0056] Step 2: The mixed mud is subjected to vacuum mud refining in a mud refiner, and the air pressure is set to 0.06 MPa;

[0057] Step 3: After refining the mud, the moisture content of the mud is adjusted to 21wt%, and then injected into a mold to form an insulator shape; then dried to a moisture content of 0.1wt%, demolded, and the insulator blank described in this comparative example is formed.

[0058] Comparative Example 2

[0059] A comparative electric porcelain blank, the raw materials include clay, porcelain powder, modified silicon dioxide powder, potassium feldspar, bauxite powder, humic acid and titanium dioxide powder; each of the raw materials is calculated by weight: 100 parts of clay, 28 parts of porcelain powder, 24 parts of modified silicon dioxide powder, 26 parts of potassium feldspar, 18 parts of bauxite powder, 0.7 parts of humic acid, and 8 parts of titanium dioxide powder. The preparation method of the modified silicon dioxide powder is:

[0060] (1) preparing an ethanol solution of tetraethyl orthosilicate; preparing a mixed solution of ammonia water and ethanol; preparing an aqueous solution of cerium nitrate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 6%, and the solvent is ethanol; the mixed solution of ammonia water and ethanol is prepared by mixing ammonia water with a solute mass percentage of 25% and anhydrous ethanol in a volume ratio of ammonia water: anhydrous ethanol = 3:1; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 9 g / L, and the solvent is water; heating the ethanol solution of tetraethyl orthosilicate to 60° C. in a water bath and keeping it warm, condensing back during the keeping warm process; flow; then, under stirring, the mixed solution of ammonia water and ethanol and the aqueous solution of cerium nitrate are added to the ethanol solution of tetraethyl orthosilicate at the same time, and the volume ratio of the mixed solution of ammonia water and ethanol and the aqueous solution of cerium nitrate added to the ethanol solution of tetraethyl orthosilicate is ethanol solution of tetraethyl orthosilicate: mixed solution of ammonia water and ethanol: aqueous solution of cerium nitrate = 10:5:2; after the addition is completed, the mixture is stirred at a constant temperature of 60°C for 80 minutes, and then allowed to stand at room temperature for 5 hours, solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and then dried at 200°C for 3 hours to obtain doped silicon dioxide powder;

[0061] (2) Add the doped silica powder to an aqueous solution of ethanol, the mass ratio of the doped silica powder to the aqueous solution of ethanol is doped silica powder: ethanol aqueous solution = 1:30; wherein the volume percentage of ethanol in the aqueous solution of ethanol is 80%, and the rest is water; stir and disperse for 20 minutes under an ultrasonic environment to obtain a dispersion; then add tannic acid to the dispersion under stirring, the mass ratio of the tannic acid added to the doped silica powder added when preparing the dispersion is doped silica powder: tannic acid = 1:0.7; after the addition is completed, adjust the pH of the dispersion to 5 (adjust with acetic acid or ammonia water with a solute mass fraction of 20%), then heat in a water bath to 80°C, stir at a constant temperature for 60 minutes, separate the solid and liquid after stirring, wash the solid phase with deionized water 3 times, and dry at 80°C for 3 hours to obtain the modified silica powder of this comparative example.

[0062] The preparation method of the above-mentioned electric porcelain blank is:

[0063] Step 1, weigh the raw materials according to the above weight proportions, mix the raw materials in a ball mill, add water and ball mill, the ball mill speed is 100r / min, the material ball water mass ratio is material: ball: water = 1:1.5:1, and the ball milling time is 10h;

[0064] Step 2: The mixed mud is subjected to vacuum mud refining in a mud refiner, and the air pressure is set to 0.06 MPa;

[0065] Step 3: After refining the mud, the moisture content of the mud is adjusted to 21wt%, and then injected into a mold to form an insulator shape; then dried to a moisture content of 0.1wt%, demolded, and the insulator blank described in this comparative example is formed.

[0066] Example 5

[0067] The dry strength of the electric porcelain blanks prepared by the methods described in the above embodiments and comparative examples was tested, and the results are shown in Table 1.

[0068] As can be seen from Table 1, the electric porcelain blank prepared by the method of the present invention has good strength, can effectively ensure the smooth progress of subsequent blank repair, glazing, kiln loading and other processes, reduce the breakage rate, and reduce the production and processing costs. The present invention firstly dopes cerium into silicon oxide, and the obtained doped silica powder has a higher specific surface area. On the one hand, it significantly increases the bonding surface between silica powder and other components in the subsequent blank, and on the other hand, it also prepares for the subsequent surface modification. Then, through tannic acid modification, a macromolecular structure is formed on the surface of the powder, so that the bonding force between silica and clay particles is enhanced, thereby improving the strength of the blank. Subsequent grafting of β-cyclodextrin can further improve the cross-linking effect between silica and other component particles, forming an irregular network structure with modified silica powder as the connecting unit, which has a good improvement effect on the strength of the blank.

[0069] Table 1

[0070] Experimental Group Dry billet strength (MPa) Example 1 8.11 Example 2 8.19 Example 3 8.23 Example 4 8.15 Comparative Example 1 6.27 Comparative Example 2 6.50

[0071] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A high-strength, lightweight, ultra-high voltage insulator blank, characterized in that: The raw materials include clay, porcelain powder, modified silicon dioxide powder, potassium feldspar, bauxite powder, humic acid and titanium dioxide powder; wherein the preparation method of the modified silicon dioxide powder is: (1) preparing an ethanol solution of tetraethyl orthosilicate; preparing a mixed solution of ammonia water and ethanol; preparing an aqueous solution of cerium nitrate; heating the ethanol solution of tetraethyl orthosilicate in a water bath to 60±5° C. and keeping it warm, condensing and refluxing during the keeping warm process; then adding the mixed solution of ammonia water and ethanol and the aqueous solution of cerium nitrate to the ethanol solution of tetraethyl orthosilicate at the same time under stirring, continuing to stir at a constant temperature of 60±5° C. for 80 to 100 minutes after the addition is completed, then standing at room temperature for more than 5 hours, separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, and then drying at 200° C. for more than 3 hours to obtain doped silicon dioxide powder; (2) adding the doped silica powder to an aqueous solution of ethanol, stirring and dispersing for more than 20 minutes under an ultrasonic environment to obtain a dispersion; then adding tannic acid to the dispersion under stirring, adjusting the pH of the dispersion to 4-6 after the addition is completed, and then heating the dispersion to 80±5° C. in a water bath, stirring at a constant temperature for more than 60 minutes, separating the solid and the liquid after the stirring is completed, washing the solid phase with deionized water for more than 3 times, and drying at 80° C. for more than 3 hours to obtain a modified powder; (3) preparing an N,N-dimethylformamide solution of β-cyclodextrin, stirring the N,N-dimethylformamide solution of β-cyclodextrin, and then adding 1,1'-carbonyldiimidazole to the solution under stirring, and continuing to stir the solution for more than 2 hours after the addition is completed, and then adding the modified powder to the solution under stirring, and continuing to stir for more than 15 hours after the addition is completed, and then separating the solid and the liquid, washing the solid phase with N,N-dimethylformamide for more than 2 times, and then washing with deionized water for more than 2 times to obtain the modified silica powder.

2. The high-strength, lightweight, ultra-high voltage insulator blank according to claim 1, characterized in that: The raw materials are calculated by weight as follows: 100 parts of clay, 20-30 parts of porcelain powder, 20-25 parts of modified silicon dioxide powder, 24-28 parts of potassium feldspar, 16-20 parts of bauxite powder, 0.6-0.8 parts of humic acid, and 6-10 parts of titanium dioxide powder.

3. The high-strength, lightweight, ultra-high voltage insulator blank according to claim 1, characterized in that: In the step (1), the mass percentage of tetraethyl orthosilicate in the ethanol solution of tetraethyl orthosilicate is 5% to 6%, and the solvent is ethanol; the mixed solution of ammonia water and ethanol is prepared by mixing ammonia water with a solute mass percentage of 25% and anhydrous ethanol in a volume ratio of ammonia water: anhydrous ethanol = 2 to 3:1; the concentration of cerium nitrate in the aqueous solution is 8 to 10 g / L.

4. The high-strength, lightweight, ultra-high voltage insulator blank according to claim 3, characterized in that: In the step (1), the volume ratio of the mixed solution of ammonia water and ethanol and the aqueous solution of cerium nitrate added to the ethanol solution of tetraethyl orthosilicate is ethanol solution of tetraethyl orthosilicate: the mixed solution of ammonia water and ethanol: the aqueous solution of cerium nitrate = 10:4-5:1-2.

5. The high-strength, lightweight, ultra-high voltage insulator blank according to claim 1, characterized in that: In the step (2), the mass ratio of the doped silica powder added to the ethanol aqueous solution is doped silica powder: ethanol aqueous solution = 1:30-40; wherein the volume percentage of ethanol in the ethanol aqueous solution is 80%-85%, and the rest is water; the mass ratio of the added mass of tannic acid to the mass ratio of the doped silica powder added when preparing the dispersion is doped silica powder: tannic acid = 1:0.5-0.

8.

6. The high-strength, lightweight, ultra-high voltage insulator blank according to claim 1, characterized in that: In the step (3), the concentration of β-cyclodextrin in the N,N-dimethylformamide solution of β-cyclodextrin is 16-20 g / L, and the solvent is N,N-dimethylformamide; the volume ratio of the added mass of the 1,1'-carbonyldiimidazole and the modified powder to the N,N-dimethylformamide solution of β-cyclodextrin is 1,1'-carbonyldiimidazole: modified powder: N,N-dimethylformamide solution of β-cyclodextrin = 3-4 g: 1-3 g: 100 mL.

Citation Information

Patent Citations

  • Preparation method of tannic acid grafted glass flakes and application of tannic acid grafted glass flakes in high-solid anticorrosive coating

    CN112226101A

  • Environment-friendly bamboo-wood composite material and preparation method thereof

    CN118879092A

  • Improvements in or relating to the manufacture of ceramic bodies

    GB748768A

  • Method for preparing white carbon black modified by silane coupling agent

    WO2012162937A1

  • Solid state forms of an organic compound

    WO2022036033A2